A qualitative study of how inter‐professional teamwork influences perioperative nursing - Thekla Holmes; Anne Vifladt; Randi Ballangrud (Wiley, 2020)
Abstract Aim To explore Norwegian operating room nurses' perceptions of how team skills in the inter‐professional operating room team influence perioperative nursing in relation to patient safety. Design A qualitative, descriptive study based on interviews. Methods Ten operating room nurses (N = 10) employed in four Norwegian hospitals were interviewed individually. A qualitative inductive content analysis was conducted. The study was reported adhering to the Consolidated Criteria for Reporting Qualitative Research Checklist. Results Three generic categories, containing three subcategories each, were identified illuminate the operating room nurses' perceptions. The operating room team's team skills influence on (a) the quality of perioperative nursing, about task performance, result for the patient and learning; (b) the progress of perioperative nursing, by keeping focus on the task, being prepared and task distribution and (c) the operating room nurses' work environment in the operating room, including confidence, stress and energy use and irritation or job satisfaction.